2019
DOI: 10.1093/ijnp/pyz008
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Genetic Knockdown of PPARδ Causes Depression-Like Behaviors and Neurogenesis Suppression

Abstract: Background Although depression is the leading cause of disability worldwide, its pathophysiology is poorly understood. Our previous study showed that hippocampal peroxisome proliferator-activated receptor δ (PPARδ) overexpression displays antidepressive effect and enhances hippocampal neurogenesis during chronic stress. Herein, we further extended our curiosity to investigate whether downregulating PPARδ could cause depressive-like behaviors through downregulation of neurogenesis. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Firstly, literature-based network analysis showed that PPARD might influence multiple molecules that functionally regulate MDD, mostly in a beneficial way (Figure 1). Our results were consistent with previous studies that PPARG plays a crucial role in regulating depression and depressive behaviors [11,12]. Most noticeably, PPARG was shown to inhibit multiple cytokine signaling pathways, which have been demonstrated to play an important role in the pathophysiology of MDD [15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Firstly, literature-based network analysis showed that PPARD might influence multiple molecules that functionally regulate MDD, mostly in a beneficial way (Figure 1). Our results were consistent with previous studies that PPARG plays a crucial role in regulating depression and depressive behaviors [11,12]. Most noticeably, PPARG was shown to inhibit multiple cytokine signaling pathways, which have been demonstrated to play an important role in the pathophysiology of MDD [15].…”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies show that PPARD might be involved in depression occurrences [11,12]. Specifically, the hippocampal genetic knockdown of PPARD has been shown to cause depression-like behaviors and neurogenesis suppression [12], suggesting that PPARD plays a crucial role in neu-rogenesis and regulates both depression and memory. Moreover, hippocampal PPARD overexpression or activation inhibits stress-induced depressive behaviors and enhances neurogenesis [11].…”
Section: Introductionmentioning
confidence: 99%
“…There is a common molecular signaling mechanism in which PPAR- γ regulates BDNF promotor activity [ 62 ]. Hippocampal PPAR- δ is involved in neurogenesis and modulates the level of BDNF [ 63 ]. The family of PPAR receptors is stimulated by fatty acids and eicosanoids and acts as transcription factors regulating gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoxins (LX) are proresolving lipid mediators derived from arachidonic acid by the action of 5- and 15-lipoxygenease (5-LOX and 15-LOX, respectively) [ 73 ]. The bioactive form 15-epi-lipoxin A 4 (15-epi LXA 4 ) promotes the resolution of inflammation by inhibiting superoxide generation and polymorphonuclear leukocyte transmigration [ 63 ]. Its role in ischemic stroke is connected with the decrease in reactive oxygen species and proinflammatory cytokine and chemokine production, blocking the adhesion to and transmigration across the endothelium, inducing apoptosis, increasing anti-inflammatory interleukins, and promoting resolution of inflammation [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPARs are a group of nuclear receptor proteins composed of PPAR-α (encoded by gene PPARA ), PPAR-δ (by PPARD ), and PPAR-γ (by PPARG ); these proteins play important roles in the differentiation, development, and metabolism of mammalian cells [ 13 ]. PPARs regulate the transportation and expression of various genes [ 14 ], which harbor variants contributing to hundreds of diseases, including different types of cancer [ 15 , 16 ], metabolic disorders [ 6 ], and multiple mental health-related conditions, such as depression [ 17 ], Parkinson’s disease [ 18 ], anxiety [ 19 ], and brain dysfunction [ 20 ]. Given the obvious importance of PPARs in core metabolic processes and in WNT signaling, both in the brain and in peripheral tissues, a relatively weak connection between variants in PPAR encoding genes and psychiatric phenotypes is surprising.…”
Section: Introductionmentioning
confidence: 99%